Substitusi Pakan Komersial dengan Ampas Kecap Ekstrusi dan Ampas Kecap Fermentasi terhadap Performans Ayam Pedaging - Widharto, Damaryanto; Gumilar, Gebby Citra Vastu (UPPM Politekik Pembangunan Pertanian Yogyakarta Magelang (Polbangtan Yoma), 2020)
The research was conducted to know influence of extruded and fermented soybean pulp in commercial feed in feed consumption, average daily gain and feed conversion. The research use 60 day old chick of broilers which were devided into 4 treatments, that is 1) were given commercial feed without substitution of extruded and fermented soybean pulp (T-0), 2) were given commercial feed with substitution of extruded soybean pulp as much as 5% (T-1), and 3) were given commercial feed with substitution of fermented soybean pulp as much as 5% (T-2). The variables observed feed consumption, average daily gain, and feed coversion. The result showed highly significant for feed consumption (P ≤ 0,01) but non significant for average daily gain and feed conversion (P ≥ 0,05) . Feed consumption is 128.08 (T-0), 106.23 (T-1), 58.77 (T-2), and 109.73 g/head/day (T-3); average daily gain is 51.95 (T-0), 46.90 (T-1), and 47.32 (T-2); feed conversion 2.51 (T-0), 2.27 (T-1), and 2.32 (T-2). Research conclusion is substtution of extruded and fermented soybean pulp in ration not yet to improve average daily gain and feed conversion, but can pressure of feed consumption.